A Novel Approach in Periodontally Accelerated Osteogenic Orthodontics (PAOO): A Case Report. Issue 3 (28th September 2018) - Soltani, Leila; Loomer, Peter M.; Chaar, Edgard El
Abstract : Introduction: The purpose of this case report was to evaluate clinical and radiographic outcomes of periodontally accelerated osteogenic orthodontics (PAOO) combined with soft tissue enhancement in a patient with thin biotype and lack of buccal plate. Case Presentation: A 46‐year‐old female was referred for periodontal risk assessment prior to orthodontic treatment. Following a comprehensive examination, including taking a cone beam computerized tomography (CBCT) the patient was identified as high risk for soft tissue recession because of prominent roots, lack of buccal plates, and thin soft tissue. The treatment was PAOO combined with soft tissue enhancement to improve hard and soft tissue support of anterior mandibular teeth. Conclusions: Clinical and radiographic evaluation after one year revealed significant improvements in hard and soft tissue phenotype. In conclusion, combination of PAOO and soft tissue grafting could be a promising treatment to improve hard and soft tissue support for orthodontic patients.